Night watch - Fairstein, Linda A. (New York : Dutton, 2012)
Forty-eight hours after Alexandra Cooper arrives in France to visit her boyfriend, Luc Rouget, her vacation in paradise is cut short when a young woman from the village is found murdered. The only evidence discovered on the body is a matchbox promoting Luc's new restaurant in New York. But before the investigation begins, Alex is summoned back to New York to handle a high profile case.
Keywords: Cooper, Alexandra (Fictitious character) -- Fiction; Public prosecutors -- Fiction; Women lawyers -- Fiction; France -- Fiction; New York (N.Y.) -- Fiction; Legal stories; Mystery fiction